PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rina Masithoh, Hapsari Muryana Titin Ruliana (EKONOMIA, 2020)
Bankruptcy is one phenomenon that often occurs in the business world. Pharmaceutical companies in Indonesia have also experienced several problems that must be faced today, such as raw materials that are still imported from abroad are a burden on companies due to high dollars, considering transactions carried out using foreign currencies. Seeing the importance of predictions regarding information about the potential for bankruptcy of the company, the authors are interested in conducting research.The purpose of this study was to find out and analyze the potential bankruptcy of pharmaceutical companies using the Altman Z-Score method.The pharmaceutical companies studied were 8 companies. The analysis technique in this study used the Z-Score method by Altman using the formula Z = 1.2 X1 + 1.4 X2 + 3.3 X3 + 0.6 X4 + 1.0 X5. The companies studied were then classified into 3 groups namely companies that did not go bankrupt (Z-Score> 2.99), companies that were vulnerable (1.81 <Z-Score <2.99), and companies that could potentially go bankrupt (Z- Score <1.81).The results of this study are for the period 2013, 2014, 2015, 2016, and 2017 stating that the 8 pharmaceutical companies studied were PT Darya-Varia Laboratoria Tbk, PT Indofarma Tbk, PT Kimia Farma Tbk, PT Kalbe Farma Tbk, PT Merck Tbk, PT Pyridam Farma Tbk, PT Industri Jamu dan Farmasi Sido Tbk, dan PT Tempo Scan Pacific Tbk fall into the category of not going bankrupt with the number of Z-Score above 2.99.Based on the conclusions that have been stated, stating that the Pharmaceutical Companies studied in the period 2013, 2014, 2015, 2016, and 2017 fall into the category of not going bankrupt with a Z-Score above 2.99. The conclusion of the research results states that the hypothesis is rejected.